Using a Standardized Clinical Quantitative Sensory Testing Battery to Judge the Clinical Relevance of Sensory Differences Between Adjacent Body Areas. Issue 1 (January 2017) - Dimova, Violeta; Oertel, Bruno G.; Lötsch, Jörn
Abstract : Background: Skin sensitivity to sensory stimuli varies among different body areas. A standardized clinical quantitative sensory testing (QST) battery, established for the diagnosis of neuropathic pain, was used to assess whether the magnitude of differences between test sites reaches clinical significance. Methods: Ten different sensory QST measures derived from thermal and mechanical stimuli were obtained from 21 healthy volunteers (10 men) and used to create somatosensory profiles bilateral from the dorsum of the hands (the standard area for the assessment of normative values for the upper extremities as proposed by the German Research Network on Neuropathic Pain) and bilateral at volar forearms as a neighboring nonstandard area. The parameters obtained were statistically compared between test sites. Results: Three of the 10 QST parameters differed significantly with respect to the "body area, " that is, warmth detection, thermal sensory limen, and mechanical pain thresholds. After z-transformation and interpretation according to the QST battery's standard instructions, 22 abnormal values were obtained at the hand. Applying the same procedure to parameters assessed at the nonstandard site forearm, that is, z-transforming them to the reference values for the hand, 24 measurements values emerged as abnormal, which was not significantly different compared with the hand ( P =0.4185). Conclusions: Sensory differences between neighboring body areas are statistically significant, reproducing prior knowledge. This has to be considered in scientific assessments where a small variation of the tested body areas may not be an option. However, the magnitude of these differences was below the difference in sensory parameters that is judged as abnormal, indicating a robustness of the QST instrument against protocol deviations with respect to the test area when using the method of comparison with a 95 % confidence interval of a reference dataset. Abstract : Supplemental Digital Content is available in the text.